2016
DOI: 10.1007/s00191-016-0459-3
|View full text |Cite
|
Sign up to set email alerts
|

The evolution of consumption and its welfare effects

Abstract: In this paper the evolution of consumption is explained on the basis of a theory that connects preferences over actions to the motivational forces driving actions. More specifically, the hypotheses about what motivates consumption activities draw on insights from biology, behavioral science, and psychology. With secularly rising income, the growing consumption opportunities and the expanding consumption alter the underlying motivational forces and induce a change of preferences. As a consequence, the structure… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
25
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(26 citation statements)
references
References 45 publications
(46 reference statements)
1
25
0
Order By: Relevance
“…This proves that income of the consumer is monotonic increasing in obtaining utility and welfare of the consumer as assumed during the construction and deriving of the model from utility function by substituting the Marshallian's Demand Function. The outcome of the study is consistent with the study of (Deaton and Muellbauer, 1986;Chai and Moneta, 2010;Kaus, 2012;and Witt, 2016) found that Engle curve is monotonic increasing in Utility of the consumer.…”
Section: Unit Root Test and Regression Analysis Of The Variablessupporting
confidence: 89%
See 1 more Smart Citation
“…This proves that income of the consumer is monotonic increasing in obtaining utility and welfare of the consumer as assumed during the construction and deriving of the model from utility function by substituting the Marshallian's Demand Function. The outcome of the study is consistent with the study of (Deaton and Muellbauer, 1986;Chai and Moneta, 2010;Kaus, 2012;and Witt, 2016) found that Engle curve is monotonic increasing in Utility of the consumer.…”
Section: Unit Root Test and Regression Analysis Of The Variablessupporting
confidence: 89%
“…The well-known studies in this regard were (Charles et al, 2009;Bierens and Pott-Buter, 1987;Atkinson et al, 1990;Lewbel, 1991;Blundell et al, 1993;Hilden, 1994;Hausman et al, 1995;and Hardle and Jerison, 1988). Witt (2016) pointed out that the consumer welfare solely depended on the behavior of the consumer choices and preferences towards opportunities of goods. The motivational factors in this regard are the income and prices of the demanded goods.…”
Section: Literature Reviewmentioning
confidence: 99%
“…From the point of view of the household management unit (microeconomic approach), the economic well-being of the individual is primarily equated with the level of consumption and, more specifically, the level of household consumption expenditure (Bartels and Urminsky, 2015;Witt, 2017;Aitken, 2019). Already Sen (1977) suggested focusing on individuals who made up a given society and stressed the need to include in welfare studies the heterogeneity of individuals due to m.in.…”
Section: Economic Welfare and Its Determinantsmentioning
confidence: 99%
“…Urban waste is one of the aspects of this crisis that hampers the sustainability of the planet due to the behavior of production and consumption resulting from economic growth [1]. The consumption of economic agents and the degree of satiety of society drive the supply chain of materials and the development of products with a shorter life cycle [2]. Consequently, increasing waste without proper disposal threatens environmental sustainability [3].…”
Section: Introductionmentioning
confidence: 99%